Spectral analysis of UV-spectrum elements in steel using portable optical emission spectrometers - Zh. N. Bankova; T. S. Birisen (Литьë и металлургия)
Optical emission spectroscopy is used to determine the mass fraction of elements such as carbon, silicon, manganese, phosphorus, sulfur, chromium, nickel, copper, aluminum, molybdenum, vanadium, titanium, arsenic, tin, boron, calcium, etc. Most of the analytical lines of the analyzed elements are located in the visible light spectrum, but the analytical lines of carbon, phosphorus and sulfur are located in the ultraviolet radiation spectrum.Ultraviolet radiation (UV radiation) is electromagnetic radiation that occupies the spectral range between visible and x ray radiation. The wavelengths of UV radiation are in the range from 10 to 400 nm. The area of UV radiation is divided into: near from 400 to 200 nm; far from 380 to 200 nm; vacuum from 200 to 10 nm.Structural particularities of the structure of the optical system of stationary spectrometers allow determining the mass fraction of chemical elements, including phosphorus and sulfur, with sufficient accuracy and reliability. This article discusses the possibility of determining the mass fractions of phosphorus and sulfur, the analytical lines of which lie in the area of ultraviolet radiation, using portable optical emission spectrometers.